Design of Image Recognition System for Rigid Suspension Chain Inventory Management. (September 2020) - Lin, Jianyu; Yu, Jianan; Pan, Lingfeng; Chen, Zhebo; Chen, Yixin; Chen, Zhenyuan
Abstract: According to the statistical requirements of automotive interior decoration system manufacturers for the rigid suspension chain digital inventory management system, this paper designs an image recognition system based on machine vision detection technology. Using the technology of feature extraction, feature matching and color recognition, this system realizes the judgment of whether each hanger on the suspension chain has suspended products, and further determines the type and color of the product. This system is connected with the digital inventory management system of suspension chain, which can update all kinds of product data information in real time and facilitate inventory statistics and analysis. At the same time, the workload will be greatly reduced with this system.